2020
DOI: 10.3389/fmicb.2020.579618
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Rapid Gene Gain and Loss in an Interhospital Outbreak of Carbapenem-Resistant Hypervirulent ST11-K64 Klebsiella pneumoniae

Abstract: We report an outbreak of carbapenemase-producing hypervirulent Klebsiella pneumoniae in two hospitals that undergo frequent patient transfers. Analysis of 11 completely assembled genomes showed that the bacteria were ST11-K64 strains. Moreover, 12 single nucleotide polymorphisms (SNPs) identified the strains as having originated from the same cluster, and were also indicative of the interhospital transmission of infection. Five plasmids were assembled in each of the strains. One plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…WGS analysis revealed that K. pneumoniae HS645 belonged to sequence type 11 (ST11), and the following acquired resistance determinants were detected: resident bla KPC-71 , bla CTX-M-65 , bla SHV-12 , bla LAP-2 , and bla TEM-1B and resistance determinants for aminoglycosides ( aadA2b and rmtB ), fluoroquinolone ( qnrS1 ), tetracycline [ tet (A)], fosfomycin ( fosA ), and sulfonamide ( sul2 ) ( Table 1 ). Plasmid DNA sequencing localized bla KPC-71 on a plasmid about 60 kb in length, which contains the resistance genes on drug resistance gene islands similar to that reported in Hunan Province in China ( 11 ). Compared with KPC-2, KPC-71 has a mutation of Ser182dup.…”
Section: Lettersupporting
confidence: 67%
“…WGS analysis revealed that K. pneumoniae HS645 belonged to sequence type 11 (ST11), and the following acquired resistance determinants were detected: resident bla KPC-71 , bla CTX-M-65 , bla SHV-12 , bla LAP-2 , and bla TEM-1B and resistance determinants for aminoglycosides ( aadA2b and rmtB ), fluoroquinolone ( qnrS1 ), tetracycline [ tet (A)], fosfomycin ( fosA ), and sulfonamide ( sul2 ) ( Table 1 ). Plasmid DNA sequencing localized bla KPC-71 on a plasmid about 60 kb in length, which contains the resistance genes on drug resistance gene islands similar to that reported in Hunan Province in China ( 11 ). Compared with KPC-2, KPC-71 has a mutation of Ser182dup.…”
Section: Lettersupporting
confidence: 67%
“…This is consistent with the increasing trend of CR-hvKP literature reports. Since the first description of CR-hvKP by Zhang et al in 2015, 10 more and more CR-hvKP literature has been reported, [17][18][19][20] mainly in the Asia-Pacific region, especially in China. CR-hvKP is a super bacterium with hypervirulence and multidrug resistance, which has great harm to people's health and high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since all the strains were collected from the same ward ICU, we speculated clonal dissemination of KPC-2-producing ST11-K64 K. pneumoniae exited, and during the process of transmission, KPC-2-producing ST11-K64 K. pneumoniae acquire of a PLVKPlike virulence plasmid, leading to KPC-2-producing ST11-K64 CR-hvKP. ZHANG et al [42] also provided evidence that ST11-K64 K.pneuminiae may be a competent host strain for a hypervirulent plasmid. The emergence of KPC-2-producing ST11-K64 CR-hvKP might pose a serious challenge to the management of elderly patients infected with these strains in the future, as these strains contain both drug resistance and virulence genes and show higher resistance than CR-non-hvKP strains [32] .…”
Section: Discussionmentioning
confidence: 99%